Erosión cervical y trauma oclusal - Rodríguez, María Isabel; Umaña Llanos, Gerardo (Revista Estomatología, 1994)
Cervical erosions have been associated to multiple etiologic factors such as oral hygiene techniques, dietary, bulimic behavior, but some of them are different and cannot be related to those causes. Lee and Eakle (1983) associate cervical erosions to lateral forces fram occlusal trauma, creating tensile and compressive stresses, affecting enamel and dettin while peripheral enamel in dento enamel junction demostratedlow tensile and high compressive stresses, dentin demostrated a reverse trend. The result is a tooth structure more susceptible to trauma, abrasion and acid dissolution.